Model-based Optimal Gearshift Strategy Design for Pure Electric Bus AMT - Guangying Jin; Mingqing Li; Baoquan Zhu (Jixie chuandong)
The pure electric bus with multi gear transmission can effectively improve the acceleration ability and driving range. However， the design of shift schedule is faced with the problems of heavy workload， high cost and over dependence on the experience of calibration engineers. Therefore， a model-based shift schedule design method， which can effectively shorten the development cycle of shift schedule is proposed. Firstly， dynamic programming is used to optimize the shift sequence of vehicles under standard cycle conditions. Then， the shift points obtained are taken as data samples， and the shift schedule that can be directly used in vehicle controller is extracted by cluster analysis method. Finally， the effectiveness of the extracted shift schedule is verified by simulation. The simulation results show that the vehicle using the shift schedule designed in this paper can give consideration to both dynamic and economy. Compared with the original shift schedule， the cycle power consumption can be reduced by 5.51%.